Writing the Experiences and (Corporeal) Knowledges of Women of Color into Educational Studies: A Colloquium - A. B. V. M. M. Armstrong-Carela-Martínez-Pérez-Ruiz Guerrero (Pedagogy & (Im)Possibilities across Education Research, 2017)
In this colloquium, we share collaborative ideas that came about during a weekend retreat. We center our discussions on Chicana and Black feminisms and Womanism, specifically addressing how women of color feminisms inspire us; imagining/defining space; tensions within our sisterhoods; transforming (inner)coloniality by embracing our lived herstories; and how Chicana and Black feminisms and Womanism transform educational studies. We leave readers with hopes for our-selves, our fields, our sisters, and for the world. While not exact tellings of our pláticas during our retreat, we capture and share the essence of burning questions, ideas, and hopes that arose for us when thinking and talking about women of color feminisms and educational studies.
Keywords: Sisterhood/s; Space; Coloniality; Educational Studies; Collective Action; Empowerment; Healing